Pengaruh Pengelolaan dan Kompetensi Sumber Daya Manusia terhadap Penyerapan Dana Kapitasi Jaminan Kesehatan Nasional Pada Pukesmas di Kabupaten Belu - Fatima Mau, Ermelinda; Perseveranda, M.E,; Paulina Bibiana, Rere; A. Manafe, Henny; Paridy, Anggraeny; Man, Stanis (Jurnal Ilmu Manajemen Terapan, 2023)
In writing this study, researchers used quantitative methods. The data used are primary data and the population and sample are 50 informants each. Data processing uses SEM based on Partial Least Square (PLS). The results of the descriptive analysis show that planning and budgeting, implementation and administration, reporting and accountability, coaching or supervision, and human resource competence are in the very good categories. The results of path analysis or statistical tests show that hypothesis 1 and hypothesis 4 are rejected. In contrast to hypothesis 2, hypothesis 3, and hypothesis 5 which have been tested show that there is a significant effect on the absorption of capitation funds with a p-value <0.05 (Hypothesis 2, 3, 5 is accepted). Based on the writing of this scientific work, the researchers suggest that the District Health Office. It is not yet possible to use this study to discuss the Health Service Strategic Plan, RKA, and the determination of DPA, especially in planning the proportion of capitation funds at the FKTP level. The health office and puskesmas must be able to carry out planning and budgeting that is integrated and by the nomenclature because it can support the achievement of the level of absorption of the JKN capitation budget.